Columnar/herringbone dual crystal packing of pyrenylsumanene and its photophysical properties - Shrestha, Binod Babu; Higashibayashi, Shuhei; Sakurai, Hidehiro (Beilstein Journal of Organic Chemistry, 2014)
A single crystal of pyrenylsumanene was found to exhibit both columnar and herringbone crystal packing. The sumanene moieties form unidirectional columnar structures based on π–π stacking while the pyrene moieties generate herringbone structures due to CH–π interactions. The absorption and emission maxima of pyrenylsumanene were both red-shifted relative to those of sumanene and pyrene, owing to the extension of π-conjugation. Monomer emission with high quantum yield (0.82) was observed for pyrenylsumanene in solution, while excimer-type red-shifted emission was evident in the crystalline phase.
Keywords: carbon nanomaterials; columnar crystal packing; fluorescence; herringbone; pyrenylsumanene